2015
DOI: 10.1093/jac/dkv301
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus θ-defensin-1 (RTD-1) exhibitsin vitroandin vivoactivity against cystic fibrosis strains ofPseudomonas aeruginosa

Abstract: This study suggests that RTD-1 is a promising potential therapeutic agent for cystic fibrosis airway disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 33 publications
(53 reference statements)
3
26
0
Order By: Relevance
“…RTD-1, the prototype -defensin, is well tolerated when administered systemically to mice and rats and is nonimmunogenic, highly stable, and effective in the arrest and resolution of autoimmune arthritis when administered as infrequently as once every 5 days (37,55). Further, studies presented here and previously reported (37,52,53,55,71) demonstrated that parenterally administered -defensins are well tolerated in mice and rats. Thus, the drug-like properties of naturally occurring -defensins represent a template for the development of antifungal agents that may prove valuable in the treatment of infections caused by MDR fungal pathogens.…”
Section: Efficacy Of -Defensins Against Mdr Candida Speciessupporting
confidence: 61%
See 1 more Smart Citation
“…RTD-1, the prototype -defensin, is well tolerated when administered systemically to mice and rats and is nonimmunogenic, highly stable, and effective in the arrest and resolution of autoimmune arthritis when administered as infrequently as once every 5 days (37,55). Further, studies presented here and previously reported (37,52,53,55,71) demonstrated that parenterally administered -defensins are well tolerated in mice and rats. Thus, the drug-like properties of naturally occurring -defensins represent a template for the development of antifungal agents that may prove valuable in the treatment of infections caused by MDR fungal pathogens.…”
Section: Efficacy Of -Defensins Against Mdr Candida Speciessupporting
confidence: 61%
“…Fifty microliters of 6% trifluoroacetic acid (TFA) was then added and incubated for 20 min at room temperature. Samples were clarified by centrifugation, supernatants were transferred to bovine serum albumin (BSA)-coated UPLC vials, and -defensin content was analyzed by UPLC-MS using an Acquity UPLC and Micromass Quattro Ultima mass spectrometer (Waters Corporation, Milford, MA), using RTD-1 as a standard, as previously described (71).…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted on a CFTR F508del-homozygous murine model of chronic P. aeruginosa lung infection indicated that treatment with Rhesus θ-defensin-1 significantly decreased lung infection and airway neutrophils [205]. Azithromycin-loaded and rapamycin-loaded nanocomposite microparticles a dry-powder-based antibiotic therapy, has been shown to enhance pulmonary antibiotic delivery [205, 206]. Recently, the use of phages, bacteria-specific viruses that kill pathogens has emerged as a promising alternative.…”
Section: Discussionmentioning
confidence: 99%
“…2015; Beringer et al. 2016). Finally, the main direct mechanisms of action proposed for the cathelicidin LL-37 have been the bacterial membrane disruption following the toroidal pore model previously commented on and the probable interference with internal targets such as DNA (Xhindoli et al.…”
Section: Direct Mechanisms Of Actionmentioning
confidence: 99%